Performance evaluation of fertigation and micronutrients on fruit yield and quality of summer tomato (Lycopersicon esculentum L.) - Akanda, MA Razzaque; Ahamad, M Shahabuddin; Rahman, MS; Halim, GMA; Hasan, MM (Bangladesh Journal of Agricultural Research, 2012)
Fertigation was found technically and economically feasible for tomato cultivation in winter as well as in summer. An experiment was conducted with summer tomato (BARI Hybrid Tomato4) having 2 drip irrigation levels with different levels of NPK and micronutrient (B, Zn, and Mg) during kharif-1 seasons of 2007 and 2008. The fertilizer levels were N100 P55 K120 kg/ha, N100 P55 K120 B1 Zn4 Mg4 kg/ha, N100 P70 K140 kg/ha and N100 P70 K140 B2 Zn6 Mg8 kg/ha and the irrigation levels were drip irrigation at 2 days interval and drip irrigation at 3 days interval. The highest marketable yield of summer tomato (35.90 t/ha and 27.12 t/ha) were obtained from the fertigation treatment with fertilizer doses of N100 P55 K120 B1 Zn4 Mg4 kg/ha irrigated at 2 days interval in 2007 and 2008. The cull yield was also the lowest (2.53 t/ha and 1.15 t/ha) in this treatment in both the years. The lowest tomato yield (20.50 t/ha and 18.29 t/ha) were obtained from the treatment with fertilizer doses N100 P70 K140 kg/ha irrigated at 2 days interval where no micronutrients were used. Fruit quality parameters like TSS, Vitamin-C and ?-carotene were also the highest for the best yielder. So, use of micronutrients with NPK showed a significant effect on quality fruits as well as yield of summer tomato. The best yielder treatment received 261.0 mm of seasonal water including an effective rainfall of 60.5 mm during the crop seasons. The highest BCR (4.41) was also found in the same treatment. Bangladesh J. Agril. Res. 37(3): 449-456, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12088